The psychological impact of COVID-19 among the undergraduate dentistry students of Sindh and Baluchistan and how they manage it. - Muhammad Mansoor Majeed; Madiha Anwar; Moti Ram Bhatia; Nabeel Khan; Mehsal Muhammad Naeem Butt; Urooj Tabassum; Muhammad Shoaib Durrani (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: The purpose of the current study was to evaluate the anxiety among the undergraduate dentistry students during the COVID-19 pandemic. It also aimed to find out their stress management strategies. Methods: A total of 809 undergraduate dentistry students of Sindh and Balochistan contributed to this web-based cross-sectional study. A validated e-questionnaire created using Google form were distributed among the dental college student through social media. Spss 22 was used for statistical analysis. Results: Significantly higher number of females and private college students were the participants. Majority of the students are dissatisfied with the online education and no significant difference is present among private and public sector dental college (p >0.05). Moderate to severe level of anxiety among both gender is prevalent. Praying and recitation of the holy book is the most common couping strategy followed by sleeping, talking to friends and family. Conclusion:- Psychological sessions should be arranged to improve the mental health of future dental surgeons. Government need to re-evaluate its policies towards the health care system and administration and teaching faculties should focus to upgrade their skill concerning e-learning